Comparative analysis of phyto-fabricated chitosan, copper oxide, and chitosan-based CuO nanoparticles: antibacterial potential against Acinetobacter baumannii isolates and anticancer activity against HepG2 cell lines - Sarfraz, Muhammad Hassan; Zubair, Muhammad; Aslam, Bilal; Ashraf, Asma; Siddique, Muhammad Hussnain; Hayat, Sumreen; Cruz, Jorrdy Neves; Muzammil, Saima; Khurshid, Mohsin; Sarfraz, Muhammad Farrukh; Hashem, Abeer; Dawoud, Turki M.; et al. (Frontiers in Microbiology, 2023)
The aim of this study was to provide a comparative analysis of chitosan (CH), copper oxide (CuO), and chitosan-based copper oxide (CH-CuO) nanoparticles for their application in the healthcare sector. The nanoparticles were synthesized by a green approach using the extract of Trianthema portulacastrum. The synthesized nanoparticles were characterized using different techniques, such as the synthesis of the particles, which was confirmed by UV–visible spectrometry that showed absorbance at 300 nm, 255 nm, and 275 nm for the CH, CuO, and CH-CuO nanoparticles, respectively. The spherical morphology of the nanoparticles and the presence of active functional groups was validated by SEM, TEM, and FTIR analysis. The crystalline nature of the particles was verified by XRD spectrum, and the average crystallite sizes of 33.54 nm, 20.13 nm, and 24.14 nm were obtained, respectively. The characterized nanoparticles were evaluated for their in vitro antibacterial and antibiofilm potential against Acinetobacter baumannii isolates, where potent activities were exhibited by the nanoparticles. The bioassay for antioxidant activity also confirmed DPPH scavenging activity for all the nanoparticles. This study also evaluated anticancer activities of the CH, CuO, and CH-CuO nanoparticles against HepG2 cell lines, where maximum inhibitions of 54, 75, and 84% were recorded, respectively. The anticancer activity was also confirmed by phase contrast microscopy, where the treated cells exhibited deformed morphologies. This study demonstrates the potential of the CH-CuO nanoparticle as an effective antibacterial agent, having with its antibiofilm activity, and in cancer treatment.